Development of a learning disabilities test a case study at elementary school - Aziz, Abdul; Jamaris, Martini; Sumadi, Tjipto (COUNS-EDU: The International Journal of Counseling and Education, 2021)
This study aims to determine the procedure and to assess the quality of the development of test instruments in measuring the learning disabilities of elementary school students. Learning disabilities are formulated as disorders that occur in learning activities such as dyslexia, dysgraphia, dyscalculia. The type of the research is research and development by using Martini Jamaris’s Model. The subjects were 90 students of elementary school in Jakarta. The number of items was 75 items consisting of 19 items (dyslexia), 29 items (dysgraphia), and 27 items (dyscalculia). The results obtained in the validity test were declared valid were only 54 of the 75 items. Reliability of the test was stated to be reliable with very high interpretation in all dimensions. The results of the analysis of learning disabilities using a learning disabilities test that have been developed were obtained 90% of students experience learning disabilities.